ORIGINAL ARTICLE PREVALENCE OF HYPERTENSION AND ASSOCIATED RISK FACTORS AMONG GOVERNMENT PRIMARY SCHOOL TEACHERS OF TALUKA SANGHAR, SINDH. : J Peop Univ Med Health Sci. 2025:15(2), 188 194.http://doi.org/10.46536/jpumhs/2025/15.02.640 - Aftab Hussain Pathan1 Altaf Khan Pathan2, Ghulam Muhammad Phull3, Abdul Manan Soomro4, Jawaid Hussain Lighari5, Masood Nabi Noor Dahri6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Health issues like hypertension are getting worse in the majority of developing nations. It is also known as the "silent killer disease" as there are no specific signs or symptoms. The most important cause of Cardiovascular disease (CVD) is Hypertension. OBJECTIVES: To determine the frequency of hypertension and the risk factors for hypertension among primary school teachers at Taluka Sanghar, Sindh. MATERIAL & METHODS: This was a cross-sectional study conducted for six months at Taluka and District Sanghar, Sindh. A total of 295 primary school teachers were included in the study. The blood pressure was measured by a mercury sphygmomanometer through the auscultatory method. The SPSS version 25.0 was used to analyze the Data. A P-value of less than 0.05 was considered significant. DURATION: July 2022 to Dec 2022 RESULT: The prevalence of hypertension among primary teachers was found to be higher in the present study. Out of 295, 88 school teachers (29.8%) were found to be hypertensive and a few 207 (70.2%) were non hypertensive. The female participants were 157 (53.2%) while male were 138(46.8%) and in the age range of 35-45 years. The risk factors found to be associated with hypertension include male gender, smoking, family history of hypertension, and BMI. CONCLUSION: The present study concluded that hypertension is common among the teachers of primary schools in Taluka Sanghar, Sindh, Pakistan. The burden of hypertension among the school teachers can be decreased by certain changes in lifestyle like quitting smoking, doing regular exercise and physical activity.